Suggestions on Relieving Physical Anxiety of Medical Workers and Improving Physical and Mental Health Under the COVID-19 Epidemic—A Case Study of Meizhou City - Lu, Zhi-Cheng; Tseng, Chien-Hsing; Lin, Hsiao-Hsien; Perng, Yuan-Shing; Tseng, Yi-Han (Frontiers in Public Health, 2022)
The study examined the effects of swimming pools on healthcare professionals' willingness to engage in recreational activities, physical anxiety, and physical and mental well-being in the context of COVID-19. The research adopted the mixed research method, used SPSS 26.0 statistical software to test the reliability of the questionnaire, and then collected 840 valid questionnaires; first analyzed the data with basic statistics, t-test, ANOVA, and PPMCC test methods, and then used the interview method to collect expert opinions. A multi-check approach assembled all data and discussions. The study found that the use of personnel dynamic tracking systems or measures, combined with sodium hypochlorite and repeated filtration to stabilize water quality, could maintain the confidence of most medical workers in the swimming pool sports environment for epidemic prevention and avoid violations. The government could formulate safety prevention and control mechanisms in traffic and establish appropriate traffic routes. Next, formulated a prescription for swimming or other physical activity mechanisms for men aged 31–50 and redesigned measures for medical staff over 51 years old to have tense head issues and physical fatigue, promote blood circulation and improve sleep quality. This will promote the purpose of relieving stress and regulating the physical and mental health of medical staff after engaging in swimming.